Compreensibilidade da informação contábil por usuários tomadores de decisão - Souza, Fabia Jaiany Viana de (2020)
Accounting can be viewed as a communication tool between the accountant and the information user. For this communication exists and achieves its objective of transmitting messages effectively, the sender must issue a message that can be understood by the receiver. The information must be aligned with their needs and elaborated in clear language and in formats that make it the disclosure transmitted directly and aimed to the intended purpose. Management accounting reports are indispensable support tools so that managers can analyze the current situation of organizations, as well as design new performance strategies and control mechanisms so that the goals established in their planning can be met. Therefore, the general objective of this thesis is to describe the comprehensibility of the accounting information of public managers and its optimization in decision making, through the reading of a more accessible complementary information presentation format. The specific objectives were: verify the informational need for decision making by managers; identify what is the presentation form and the most appropriate transmission means for accounting information to be presented; analyze the purpose of using accounting information in surveyed subjects daily life; identify the favorable and unfavorable points regarding the accounting information reading in the presentation format proposed in the research, according to the managers opinion. Considering the presentation format of accounting information and communication theory and cognitive load theory, we have the thesis that when dealing with accounting information through a more accessible complementary format, public managers can better understand accounting information and, later, have more use of them for decision making. The thesis is classified as a multicase, exploratory, and descriptive study with a qualitative approach. The field of study of the research corresponded to seven campuses of the Federal Institute of Education, Science, and Technology of Rio Grande do Norte (IFRN). For data collection, two research instruments were applied, composed of a questionnaire and another formed by decision-making scenarios, so that it could analyze the respondents' perception when reading the accounting information in two presentation formats. As a data analysis technique, content analysis was used together with the Iramuteq software. The results revealed that the graphics is among the most mentioned accessibility tools among the study participants, being the one that most facilitated the understanding of the accounting information used in the management report. It was found that the explanatory audio was not considered as an element of accessibility for the accounting information presentation, and it is still possible to observe suggestions for incorporating the use of projections in the historical series of transmitted accounting information, as well as the use of narrative text for complement the budget execution information presented through tables and graphs. Therefore, the visual cognitive resource was the one that had the highest acceptance for the surveyed managers.